2017
DOI: 10.5152/eurasianjmed.2016.0259
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial and Ovarian Cancer with MR Imaging Importance of Serum HE4 and CA 125 Levels in the Extent of Disease at Evaluation

Abstract: Objective: Currently, no clinically useful tumor marker is available for primary diagnosis in endometrial cancer. Human epididymis protein-4 (HE-4) has high sensitivity and specificity as a tumor marker. Further, HE-4 has been shown to be elevated in early stage endometrial cancer and is more sensitive than CA 125. In our study, CA 125 and HE-4 reputation as a tumor marker for diagnosis of ovarian and endometrial cancer with the use of both the availability and affect the way we investigated the rate of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The literature regarding the benefit of combining HE4 and CA125 for detection of EC is mixed. Several studies have shown a nonsignificant increase in sensitivity of the combination of serum HE4+CA125 for detection of EC compared to using HE4 alone [26,29,115], but this comes at a cost to specificity [38,48]. In contrast, other studies have shown no significant difference combining serum HE4 and CA125 compared to HE4 alone for EC detection [27,35].…”
Section: He4 In Combination With Other Markersmentioning
confidence: 99%
“…The literature regarding the benefit of combining HE4 and CA125 for detection of EC is mixed. Several studies have shown a nonsignificant increase in sensitivity of the combination of serum HE4+CA125 for detection of EC compared to using HE4 alone [26,29,115], but this comes at a cost to specificity [38,48]. In contrast, other studies have shown no significant difference combining serum HE4 and CA125 compared to HE4 alone for EC detection [27,35].…”
Section: He4 In Combination With Other Markersmentioning
confidence: 99%